Factors Affecting Interest in Stock Investment for Millennial Generation (Study on Accounting Study Program Students, University of Muhammadiyah Sidoarjo) - Siti Mei Nur Rosita; Aisha Hanif (Journal of Islamic and Muhammadiyah Studies, 2023)
This study aims to determine whether the variables of investment knowledge, investment motivation, financial literacy, and risk affect interest in stock investment. The research method used is quantitative with multiple linear regression analysis as an analytical tool, to prove the hypothesis used by testing the validity, reliability, coefficient of determinant and multiple linear regression analysis with significant test f and t. The sampling technique used is purposive sampling by distributing questionnaires via google form so that it gets 82 respondents and this research was conducted on students of the Accounting Study Program, Muhammadiyah University of Sidoarjo. The results show that the results of the F test of the investment interest variable can be influenced by the variables of Investment Knowledge (X1), Investment Motivation (X2), Financial Literacy (X3) and Risk (X4) together. By partial test, the variables of Investment Knowledge (X1), Investment Motivation (X2), Financial Literacy (X3) and Risk (X4) have a significant effect on investment interest.